2021
DOI: 10.3390/su13031405
|View full text |Cite
|
Sign up to set email alerts
|

Beauty and Celebrity: Korean Entertainment and Its Impacts on Female Indonesian Viewers’ Consumption Intentions

Abstract: The Korean entertainment industry’s popularity and global reach has prompted private companies and destination management organizations to place Korean products and position Korea as a destination to international viewers. Korean celebrities have also been found to form positively perceived Korean beauty standards, consequently serving as an antecedent of Korean beauty product awareness and perceived beauty product quality among international audiences. Although previous studies have found that audience involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 71 publications
1
24
0
4
Order By: Relevance
“…The reference groups among the samples may have conflicting approvals to the sample's internal preferences. Previous research has also found that popular culture such as music and other mass media are the main driving force in increasing Korea's image among the young people abroad [78,86,88]. Thus, such influence may not be the usual attribute of a destination for education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reference groups among the samples may have conflicting approvals to the sample's internal preferences. Previous research has also found that popular culture such as music and other mass media are the main driving force in increasing Korea's image among the young people abroad [78,86,88]. Thus, such influence may not be the usual attribute of a destination for education.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, an individual's personal motivation is often shaped by the external environments [61,73,[75][76][77]. Evidence from previous studies includes how expectations from parents and how the social image of successful people ultimately influence an individual to pursue education or lifestyle activities [12,16,22,78]. In the present research, the three interpersonal constructs (Veblen, snob, and bandwagon) were assumed to impact the two personal motivation constructs (hedonism and perfectionism).…”
Section: Hedonic Effectmentioning
confidence: 91%
“…Prior studies (Amos et al, 2008;Sonwalkar et al, 2011) have observed that celebrity traits affect the enhanced cash inflows (Ding et al, 2011), incremental profits, and related gains (Prentice and Zhang, 2017). Previous research on celebrities primarily focuses on two types: entertainment celebrities (Halim and Kiatkawsin, 2021;Hwang, 2010) and sports celebrities (Felbert and Breuer, 2021;Dik cius and Ilciukiene, 2021). The significant contribution of these entertainment and sports celebrities indicated an overall positive impact on the advertisement outcomes in terms of consumers' purchase intentions.…”
Section: Stock Investment Intentionsmentioning
confidence: 99%
“…Regarding the purchase intention variable, this was based on the items proposed by [74,75]. As for the EWOM and involvement variables, they were based on the items used by [76].…”
Section: Sample and Measurement Instrumentmentioning
confidence: 99%